2019
DOI: 10.1155/2019/9712816
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Histopathological Examination to the Final Diagnosis of Peripheral Odontogenic Tumors: A Case Report of a Peripheral Odontoma

Abstract: A 30-year-old Caucasian man presented with an 18-month history of an asymptomatic calcified mass, located on the buccal side of the alveolar ridge. Medical records did not present any underlying conditions. On intraoral examination, the lesion was located on the right side of the maxilla, showing mucosal fenestration with mineralized tissue measuring approximately 1 cm in diameter. Radiographic examination showed multiple radiopaque masses. Incisional biopsy was performed, and histological analysis revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several dentitional anomalies can refer to the presence of an odontoma; persisting deciduous tooth, delayed tooth eruption and missing or impacted permanent tooth. In certain cases, a growing odontoma may break through the gingival mucosa and the appearance of a hard tissue tumor in the fenestration mimics a tooth eruption [6,10]. In the presented case, an unusual inflammatory process associated with an anomalous tooth eruption suggested the presence of jaw tumor.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several dentitional anomalies can refer to the presence of an odontoma; persisting deciduous tooth, delayed tooth eruption and missing or impacted permanent tooth. In certain cases, a growing odontoma may break through the gingival mucosa and the appearance of a hard tissue tumor in the fenestration mimics a tooth eruption [6,10]. In the presented case, an unusual inflammatory process associated with an anomalous tooth eruption suggested the presence of jaw tumor.…”
Section: Introductionmentioning
confidence: 67%
“…Central odontoma is located intraosseusly, while the extremely rare peripheral odontoma can be found in the soft tissues. Both lesions are more prevalent in the anterior region of maxilla and mandible, with nearly a same incidence rate in both jaws [5][6][7]. Gender predilection of the incidence of odontoma could not be revealed [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no consensus about the stimuli that could activate the epithelial remnants and initiate the proliferation for PO. Trauma, infection, hereditary influence, and genetic alterations associated or otherwise with hereditary conditions (Gardner syndrome and Hermanns syndrome) are also possible triggers [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Etiopathological Theoriesmentioning
confidence: 99%
“…In addition, de Oliveira et al reported a rare case of erupted PO in a 30-year-old male patient, localized on the buccal side of the alveolar ridge and erupted almost 18 months before the clinical diagnosis and described as asymptomatic calcified mass. Radiographic images showed multiple radiopaque masses and an incisional biopsy was performed due to the patient's refusal to completely remove the lesion [25]. Moghadam et al described a case of a peripheral developing odontoma in a healthy 8-year-old girl, presenting as an isolated and ulcerated soft tissue mass of the palatal gingiva in the region of the right canine and deciduous first molar.…”
Section: Peripheral Developing Odontoma In Pediatric and Adult Patien...mentioning
confidence: 99%
“…Though evidence of odontogenic tissue and hard tissue formation in the lesion is an indication of an odontoma. However, clinical, and morphological findings frequently reveal significant hard tissue disorganizations in the odontogenic lesion that justify the diagnosis of an odontoma (22,31,32). Indeed, the shape and appearance of the odontoma may be reminiscent of a tooth, but the sum of the findings misses the individual characteristics of a functional tooth (22,33,34).…”
Section: Imaging Of Ectopic Teeth On Radiographsmentioning
confidence: 99%